PENGARUH MODEL PEMBELAJARAN RADEC TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS V SD INPRES 6/75 PANCAITANA KABUPATEN BONE - Abd. Hafid; Awaluddin Muin; Andi Risna Rabiul Duhaeni (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is a quantitative study that aims to determine the effect of using the RADEC learning model on the ability to write explanatory texts of fifth grade students of SD Inpres 6/75 Pancaitana, Bone Regency. This type of research is Pre-Experimental design with One-Group Pretest-Posttest form. The independent variable in this study is the RADEC learning model (X), while the dependent variable is the ability to write explanatory text (Y) with a total of 21 students. The data collection technique used was a 2-time test to determine students' ability to write explanatory text before and after using the RADEC Learning model. Data analysis used descriptive statistical analysis and inferential statistical analysis. The results of descriptive statistical analysis showed that before applying the RADEC learning model, the average student pretest score was 49.19 which was in the sufficient category and after applying the RADEC Learning model, the student posttest results increased with an average of 79.10 which was in the good category. From the results of inferential statistical analysis, the pretest and posttest data obtained by students were normally distributed and homogeneous, besides the results of hypothesis testing showed a difference in students' ability to write explanatory text before and after applying the RADEC learning model. The conclusion of this study is that there is a significant effect of the RADEC learning model on the ability to write explanatory texts of fifth grade students of SD Inpres 6/75 Pancaitana, Bone Regency.